Yuca: Control integrado de plagas - Reyes, J.A. (International Center for Tropical Agriculture, 1983)
Due to the increasing extension of areas planted to cassava in tropical countries, the maintenance of biological equilibrium through adequate integrated control techniques becomes imperative as well as the collection of data on var. resistance, biological control, and cultural practices. Basic information for integrated pest control is given. Arthropods attacking cassava are described regarding yield losses, biology, morphology, and ecology. Criteria for the establishment of a control program on var. resistance are discussed and techniques for germplasm evaluation and new developments on var. resistance to mites and insects are described. Biological control is discussed in detail: beneficial agents and their use, population studies, identification and management of hyperparasites. A conceptual framework is provided and recommendations are given for the control of economically important pests. Mass rearing techniques and methods for the collection, handling, and establishment of beneficial agents are included. (CIAT)